Shot moment in optoelectronic training in the air-pistol shooting - Zanevskyy, I.; Korostylova, Y.; Mykhaylov, V. (International Journal of Sports Science and Engineering, 2010)
The aim of the research is to study the interdependence between the shot moment parameter and the result in shooting simulator training. The article considers the problem of the relationships between a shot moment parameter and a virtual result in training with the SCATT optoelectronic shooting simulator. Special technique is proposed and the experimental investigation with the parallel fixation of sighting point coordinates location and the hole centres on a real target and a SCATT virtual target has been conducted. The model of pellet internal ballistics in a barrel is developed. The calculated method that defines the parameters of virtual holes location imitation on the optoelectronic target at the specific shot moment is substantiated.